Quasi-ordered plasmonic metasurfaces with unclonable stochastic scattering for secure authentication - Gyurin Kim; Doeun Kim; JuHyeong Lee; Juhwan Kim; Se-Yeon Heo; Young Min Song; Hyeon-Ho Jeong (Nature Communications)
Abstract Quasi-order in structural coloration, as observed in nature, offers intrinsic, unclonable near-field stochastic fingerprints while preserving far-field uniform colors. However, replicating this balance in artificial photonic metasurfaces remains a major challenge. Here, we present plasmonic metasurfaces that achieve this balance through electrostatic self-assembly of quasi-ordered gold nanoparticles onto a dielectric-spaced metallic mirror. These metasurfaces enable precise tuning of far-field reflective colors across the visible spectrum by adjusting the dielectric gap thickness, while simultaneously generating stochastic near-field scattering patterns that serve as unique physically unclonable functions (PUFs). The resulting scattering PUF keys exhibit uniform bit uniformity (average: 0.501), high uniqueness (inter-Hamming distance: 0.496) and large capacity (~10260), with strong environmental stability and resistance to unauthorized cloning. We further demonstrate the practical applications of these plasmonic metasurfaces in security and authentication, including information camouflage and the integration of hidden PUF keys into identification cards and quick-response codes.